Kynurenine Pathway Metabolites in Alzheimer's Disease - Giil, Lasse Melvaer; Midttun, Øivind; Refsum, Helga; Ulvik, Arve; Advani, Rajiv; Smith, A David; Ueland, Per Magne (Journal of Alzheimer's disease, 2017)
Metabolites of tryptophan, produced via the kynurenine pathway (kynurenines), have been linked to Alzheimer's disease (AD) in small cohorts with conflicting results. To compare differences in plasma kynurenine levels between AD and controls and identify potential associations with cognition. The study included 65 histopathologically-confirmed AD patients and 65 cognitively-screened controls from the Oxford Project to Investigate Memory and Ageing (OPTIMA) cohort. Cognition was assessed using the Cambridge Cognitive Examination (CamCog). Tryptophan, kynurenines, neopterin, and vitamin B6 forms were measured in plasma by liquid chromatography-tandem mass spectrometry. Non-parametric statistics, logistic regression and standardized robust regressions were applied with a false discovery rate of 0.05. Tryptophan, xanthurenic acid, 3-hydroxyanthranilic acid, and quinolinic acid were lower in AD (Odds ratios (ORs) 0.24 -0.47; p-values <0.001 -0.01). Pyridoxal 5'phosphate did not differ between AD and controls. Kynurenine, anthranilic acid, quinolinic acid, and markers of immune activation (neopterin, kynurenine/tryptophan ratio, and the PAr index (Pyridoxic acid/(Pyridoxal 5'phosphate + Pyridoxal)) increased with age (β 0.31 -0.51; p-values <0.001 -0.006). Xanthurenic acid decreased with age (β: -0.42, p < 0.001). Elderly AD patients with high quinolinic acid performed worse on the CamCog test, indicated by a significant age*quinolinic acid interaction (β 0.21, p < 0.001). Plasma concentrations of several kynurenines were lower in patients with AD compared to controls. Low xanthurenic acid occurred in both AD and with aging. Inflammation-related markers were associated with age, but not AD. However, elevated QA was associated with poor cognition in older AD patients.